RUSSIAN ENERGY HEGEMONY IN CENTRAL ASIA - Asri Surya Suci Lestari (HI 16 UMY 101, 2016)
*101Russia is one of the biggest natural resources producers in the world. However, Russia involved in the development of Central Asian natural resources. Russia wants to maintain security and stability in Central Asia to prevent any problems that will make spillover effect in the region and harm Russia’s interest. Stability in Central Asia will help with the oil import activity from Central Asian countries to Russia. Russia wants to keep Central Asia in its influence not only for energy security but also in other areas. Russia does not want the Central Asian countries to have another pipeline route to other neighboring countries This paper will analyze how Russia maintains its hegemony in Central Asian energy through certain strategies. As former Soviet Union states, Russia and Central Asia share the same history and culture. Strategic location of Russia enable it to keep Central Asian countries dependent on Russian pipeline to transport their energy. Many multilateral and bilateral agreement on energy sector done by Russia and Central Asian countries.